Analisis Transparansi Dana Desa Lombuza’ua dalam Mewujudkan Pembangunan Desa - Harefa, Elpiana; Lumban Tobing, Artha; Primawati, Laurencia (Green Publisher Indonesia, 2025)
Village development in Indonesia is strengthened by Law No. 6/2014 and the Village Fund from the national budget for community welfare and infrastructure. The transparency of Village Fund management is crucial to its effectiveness. This research analyzes transparency in Lombuza'ua Village, Lotu Sub-district, with a focus on information accessibility, public discourse, process openness, and data availability.This research uses descriptive qualitative methods to understand the transparency of Village Fund management in Lombuza'ua Village based on four key indicators. Data were obtained through observations, interviews, and literature studies, with informants selected purposively. The analysis was conducted inductively through data reduction, presentation, and verification to reveal the factors influencing the transparency of the Village Fund.The study found that transparency of the Village Fund in Lombuza'ua Village plays an important role in accountable village development. Information is conveyed through various media, but there are still obstacles in digital accessibility and community understanding. Citizen participation in oversight is increasing, although there are challenges in public trust. This research highlights the importance of transparency in Village Fund management in Lombuza'ua Village for sustainable development. Transparency improves public trust, fund accountability and citizen participation. However, challenges such as limited access to information, weak supervision, and human resource capacity still exist.